Integrated CFD and Aspen Plus Simulation for Optimizing Biomass Combustion: A Study on Sugarcane Bagasse - Nugraha, Maulana Gilar; Azarya, Eblin Alle; Hidayat, Muslikhin; Saptoadi, Harwin (Journal of Engineering and Technological Sciences, 2025)
This study presents an integrated simulation approach to optimize biomass combustion using sugarcane bagasse as a renewable feedstock. Computational fluid dynamics (CFD) was employed to model combustion hydrodynamics, while Aspen Plus was used to simulate pyrolysis product distribution based on Gibbs free energy minimization. The simulation involved key parameters such as air-fuel ratio, excess air level (100% and 200%), and combustion temperature profiles, which were validated against experimental data from a lab-scale grate-fired furnace. The pyrolysis results revealed that increasing the temperature from 400°C to 600°C significantly enhanced CO and H₂ concentrations, thereby improving syngas reactivity. CFD analysis showed that, at 100% excess air, CO₂ concentration reached 9.15% with an average freeboard temperature of 405.2°C, while at 200% excess air, the CO₂ dropped to 6.46% and the temperature decreased to 397.9°C, indicating reduced combustion efficiency. These results underscore the importance of optimizing air supply to enhance combustion performance and minimize unburnt volatiles. The findings confirm that integrating CFD and Aspen Plus simulations provides a reliable framework for improving the efficiency and environmental performance of biomass combustion systems.